2017
DOI: 10.3389/fneur.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Tolerability of the Clonidine Transdermal Patch in the Treatment for Children with Tic Disorders: A Prospective, Open, Single-Group, Self-Controlled Study

Abstract: BackgroundTo evaluate the efficacy and tolerability of a clonidine transdermal patch in the treatment of children with tic disorders (TD) and to establish a predictive model for patients.MethodsForty-one patients who met the inclusion criteria entered into 12 weeks of prospective, open, single-group, self-controlled treatment with a clonidine transdermal patch. The Yale Global Tic Severity Scale (YGTSS) was employed before therapy (baseline) and at 4, 8, and 12 weeks after therapy.Results(1) The total effect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…21 It is thought to reduce tics through the resultant decrease of norepinephrine release and turnover. 22 Clonidine offers a therapeutic option without the risks of drug-induced movement disorders that can be associated with antipsychotic drugs. However, evidence supporting the efficacy of clonidine is inconsistent and is often based on small numbers of patients.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 It is thought to reduce tics through the resultant decrease of norepinephrine release and turnover. 22 Clonidine offers a therapeutic option without the risks of drug-induced movement disorders that can be associated with antipsychotic drugs. However, evidence supporting the efficacy of clonidine is inconsistent and is often based on small numbers of patients.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…The YGTSS is a widely used, semi-structured and clinician-rated measure of the severity of tic characteristics, including the number, frequency, intensity, complexity, and their interference with lifestyle. 5,22 YGTSS total scores combine the measured effect on motor tic, vocal tic, and overall improvements. In addition, changes in Clinical Global Impression rating scale scores (CGI), which provide a separate improvement rating and a summation of YGTSS subscores, were also reported.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although early studies of the effectiveness of clonidine were mixed [58], clonidine has been shown to be more effective than placebo at reducing tics [59] and additionally helps improve tics in patients with comorbid TS and ADHD [60]. The clonidine adhesive patch has additionally been shown to be safe and effective for TS management [61][62][63] and is comparable to haloperidol [64][65][66]. Guanfacine has had mixed results with some studies demonstrating safety and efficacy [67,68], but others not demonstrating significant tic reduction [69,70].…”
Section: Alpha-2-adrenergic Agonistsmentioning
confidence: 99%
“…As far as pharmacological therapy is concerned, clonidine, an alpha agonist, is useful in treating Tourette's syndrome. Clonidine transdermal patch has no peak plasma concentration, which is used continuously for a week to have maximum efficacy and fewer side effects [ 10 ]. Antipsychotics such as aripiprazole improve tics in patients suffering from TS with OCD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%